ANALISIS STRATEGI MODEL BOSTON CONSULTING GROUP (BCG) PT. TRIMITRA BATERAI PRAKASA - Ahmad Sutisna; Sunarmo (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
Every company is currently competing to market its own products and advantages, therefore every company must optimize its business strategy in order to achieve company goals. This research was conducted with the aim of knowing: (1) The company's position in the 2018-2021 BCG matrix. (2) The business strategy that the company should implement in the future after knowing the company's position in the BCG matrix. The data collection method used was field research methods such as interviews with the forum group discussion (FGD) approach, observation, documentation, and triangulation. The data approach in this study was carried out in a qualitative descriptive manner. The data used are primary data and secondary data. Then the data were analyzed with the Boston Consulting Group (BCG) matrix analysis. From the results of research with BCG matrix analysis, it can be seen that the average market growth rate of PT. Trimitra Baterai Prakasa is quite low at -5.5% and the market share value is relatively low at 0.43x. Then PT. Trimitra Baterai Prakasa is in the dog quadrant. The strategy that can be used by PT. Trimitra Baterai Prakasa is a divest strategy